Working to the Beat: A Self-Regulatory Framework Linking Music Characteristics to Job Performance - Keeler, Kathleen R.; Cortina, Jose M. (Academy of Management Review, 2020)
With changes in musical technology, it is increasingly common for employees to listen to music at work. Research from a wide variety of scientific fields has demonstrated that music affects our behavior through various physiological, affective, and cognitive processes. Despite this abundance of research, the organizational sciences have largely ignored the implications of listening to music at work. We draw on self-regulation theory to argue that characteristics of music (i.e., musical key, tempo, complexity, volume) influence job performance through cognitive self-regulatory processes (i.e., executive functions). We explain how music, via its physiological and affective consequences, can influence executive functions, and how, in turn, this impacts various task performance outcomes. We conclude by describing implications for organizations with regard to allowing or even encouraging employees to listen to music at work and offer suggestions for future research.